Reassessing the variability in atmospheric H2 using the two‐way nested TM5 model. Issue 9 (8th May 2013) - Pieterse, G.; Krol, M. C.; Batenburg, A. M.; M. Brenninkmeijer, C. A.; Popa, M. E.; O'Doherty, S.; Grant, A.; Steele, L. P.; Krummel, P. B.; Langenfelds, R. L.; Wang, H. J.; Vermeulen, A. T.; et al.
Abstract : [1] This work reassesses the global atmospheric budget of H2 with the TM5 model. The recent adjustment of the calibration scale for H2 translates into a change in the tropospheric burden. Furthermore, the ECMWF Reanalysis‐Interim (ERA‐Interim) data from the European Centre for Medium‐Range Weather Forecasts (ECMWF) used in this study show slower vertical transport than the operational data used before. Consequently, more H2 is removed by deposition. The deposition parametrization is updated because significant deposition fluxes for snow, water, and vegetation surfaces were calculated in our previous study. Timescales of 1–2 h are asserted for the transport of H2 through the canopies of densely vegetated regions. The global scale variability of H2 and δ [ D H2 ] is well represented by the updated model. H2 is slightly overestimated in the Southern Hemisphere because too little H2 is removed by dry deposition to rainforests and savannahs. The variability in H2 over Europe is further investigated using a high‐resolution model subdomain. It is shown that discrepancies between the model and the observations are mainly caused by the finite model resolution. The tropospheric burden is estimated at 165±8 Tg H2 . The removal rates of H2 by deposition and photochemical oxidation are estimated at 53±4 and 23±2 Tg H2 /yr, resulting in a tropospheric lifetime of 2.2±0.2 year. Key Points: Global and regional model validation for H2 Re‐evaluation global budget of H2 Relevance of using common calibration scale